Comparative Study of Tortfeasor, s Civil Liability to Bystander in the U.S Legal system and Bringing it up in Iranian Legal System - Abbas Mirshekari; Zahra Takhshid; Mona Abdi (پژوهشنامه حقوق تطبیقی, 2024)
Imagine that A has witnessed an incident in which B injures or kills C. It is undoubtedly painful to witness, but does it also follow that one can recover damages for suffering emotional distress as the result of witnessing the accident? The recognition of the tort of negligent infliction of emotional harm, also known as NIED, has been one of the ways that tort law has attempted to provide a remedy for the emotionally injured. Nevertheless, the relatively new tort has raised many questions. In the U.S. legal system, different criteria have been proposed over the years to allow for NIED liability. For example, the impact rule and the zone of danger have been amongst the most popular. This Article focuses on the latest exception which is the bystander liability and its evolution. It is the liability to a person who witnesses a person being injured or killed due to the carelessness of another person. This Article compares the U.S. common law precedent with Iran’s civil liability regime and concludes that bystander emotional harm can also be recognized as a valid cause of action for redressing this type of emotional harm in the Iranian legal system. Bystander liability comes with the caveat of close relationship between the bystander and the injured individual. As such, this requirement should be based on the norms of the community that may differ from one another.